CULTURAL UNIQUENESS IN MASABEDE AND KADUGOLLA DIVINE RELATIONSHIPS - P, Palaya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
For the Masabede and Kadugolla tribes, 'God is the Panchaprana' is omniscient and worships innumerable gods. Originally, these two tribes belonged to the Vaishnava or Shaiva sect, which is an inextricable entanglement. Those who were herdsmen, who were nomads in search of grass and water in the past, are the gods placed in bamboo boxes to facilitate transportation. If we see that there are equal numbers of Shaiva and Vaishnava gods among the gods that they brought with them when they migrated, we can see the divine confluence of Shaiva and Vaishnava. The deities celebrated by Masabeders are Nalujaruva of Challakere taluk, Bosedeva of Bosedevarahatti, Peddathirumaladev of Bedreddihalli, Kampalarangaswamy of Kampaladevarahatti and others like Katamlingeshwar of Katappanahatti of Challakere taluk and Bommalinga of Gaurasamudra Deities such as Shvara, Pamudlu Gurunath of Pamudlu Bedag of Obanahalli, etc. are identified as important deities in this part. Similarly, Saha deities are also found in Kadugollar who are of Yadava descent. The deities they worship in the Challakere area are Kadarinarasimha Swami, Junjappa (the home deity of Kadigollar), Ettappa, Chittappa, Halappa, Chikkannaschami, Banjigere Eranna, Siddhaiah, Katappa, Iramuddappa, Nagappa, Bhutappa, Patappa, Kaytappa, Thimmappa, Chitradeva and others. Although identified as worshipers of Vishnu with the celebration, Saha is also identified as Saiva worshipers with the worship of Shaiva deities. Shiva worshipers wear Nama on their foreheads, Vishnu worshipers wear Vibhuti.